2018
DOI: 10.1186/s12877-018-0814-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive pharmaceutical care to prevent drug-related readmissions of dependent-living elderly patients: a randomized controlled trial

Abstract: BackgroundElderly patients are vulnerable to adverse drug reactions (ADRs). Drug-related readmissions (DRRs) can be a major consequence of ADR. Therefore, this study aimed to investigate the effects of a ward-based, comprehensive pharmaceutical care service on the occurrence of DRRs as the endpoint in dependent-living elderly patients.MethodsA randomized, controlled trial was performed at a German University Hospital. Patients fulfilling the following criteria were eligible: admission to a cooperating ward, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 29 publications
(41 reference statements)
0
37
0
3
Order By: Relevance
“…Only one study showed a statistically significant improvement in medication‐related hospital admissions in the primary analysis, whereas 3 showed improvement after post hoc analysis …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Only one study showed a statistically significant improvement in medication‐related hospital admissions in the primary analysis, whereas 3 showed improvement after post hoc analysis …”
Section: Resultsmentioning
confidence: 97%
“…The most commonly occurring CFIR domain was the inner setting. Within this domain, the most commonly occurring construct was Networks and Communication (seven papers) . Networks and Communication included topics such as the relationship between the pharmacist and the rest of the care team, which was the single most commonly identified implementation determinant identified in the papers that were reviewed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 21 Regarding the effect on hospital readmissions and other clinical outcomes, review data are less consistent and incorporate few randomised controlled trials (RCTs) [22][23][24] ; however, there are relatively recent findings indicating that medication reviews conducted by clinical pharmacists on the ward can reduce drug-related readmissions to hospital in various groups of elderly people. [25][26][27] Postdischarge interventions involving phone-based follow-ups by clinical pharmacists have reduced all-cause readmission rates, but these trials did not specifically target an elderly population. 28 29 In addition, there seems to be a need for more RCTs that target medication discrepancies and errors during care transitions between hospital and primary care.…”
Section: Introductionmentioning
confidence: 99%